Tissue factor deficiency increases alveolar hemorrhage and death in influenza A virus‐infected mice. (5th April 2016) - Antoniak, S.; Tatsumi, K.; Hisada, Y.; Milner, J. J.; Neidich, S. D.; Shaver, C. M.; Pawlinski, R.; Beck, M. A.; Bastarache, J. A.; Mackman, N.
Abstract : Essentials H1N1 Influenza A virus (IAV) infection is a hemostatic challenge for the lung. Tissue factor (TF) on lung epithelial cells maintains lung hemostasis after IAV infection. Reduced TF‐dependent activation of coagulation leads to alveolar hemorrhage. Anticoagulation might increase the risk for hemorrhages into the lung during severe IAV infection. Summary: Background: Influenza A virus (IAV) infection is a common respiratory tract infection that causes considerable morbidity and mortality worldwide. Objective: To investigate the effect of genetic deficiency of tissue factor (TF) in a mouse model of IAV infection. Methods: Wild‐type mice, low‐TF (LTF) mice and mice with the TF gene deleted in different cell types were infected with a mouse‐adapted A/Puerto Rico/8/34 H1N1 strain of IAV. TF expression was measured in the lungs, and bronchoalveolar lavage fluid (BALF) was collected to measure extracellular vesicle TF, activation of coagulation, alveolar hemorrhage, and inflammation. Results: IAV infection of wild‐type mice increased lung TF expression, activation of coagulation and inflammation in BALF, but also led to alveolar hemorrhage. LTF mice and mice with selective deficiency of TF in lung epithelial cells had low basal levels of TF and failed to increase TF expression after infection; these two strains of mice had more alveolar hemorrhage and death than controls. In contrast, deletion of TF in either myeloid cells or endothelial cells and hematopoietic cells did not increase alveolar hemorrhage or death after IAV infection. These results indicate that TF expression in the lung, particularly in epithelial cells, is required to maintain alveolar hemostasis after IAV infection. Conclusion: Our study indicates that TF‐dependent activation of coagulation is required to limit alveolar hemorrhage and death after IAV infection.